Recovery After Genocide: Understanding the Dimensions of Recovery Capital Among Incarcerated Genocide Perpetrators in Rwanda - Barnes-Ceeney, Kevin; Gideon, Lior; Leitch, Laurie; Yasuhara, Kento (Frontiers in Psychology, 2019)
Utilizing survey data from 302 men and women incarcerated in the Rwandan correctional system for the crime of genocide, and structured interviews with 75 prisoners, this mixed methods study draws on the concept of recovery capital to understand how individuals convicted of genocide navigate post-genocide healing. Genocide smashes physical and human capital and perverts social and cultural capital. Experiencing high levels of posttraumatic stress symptoms with more than two-thirds of the sample scoring above typical civilian cut-off levels, raised levels of depression, and high levels of anxiety, and failing physical health, the genocide perpetrators require multiple sources of recovery capital to foster internal resilience as they look forward to rebuilding their own lives.